(3GdCdbGHs - (3YHO Gddg Hf eMeO Hf jhSa Hf fUQ GdGROj, CHh GdhdjO ,GHf GdaQVj,J (B403 (3g` s
(3ChdgG (B:s
(3efJNH ef cJGH GdCdbGH hHYOg PcQ HSfOg Yf CHj LHjQI Hf GdVMGc bGd (B: (3cGf Cgd GdLGgdjI jSehf GdQLd HGdCSeGA s
(3BNQgG (B:s
(3heeG cJH aVd Hf GdMGaX gPG GdMOjK SQ Hg SQhQkG TOjOkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B125 - (3U(B162s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B121s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs